CREATION OF THE QUINUA BRAND OF THE COMPANY SUMAK TARPUY AS A POSITIONING STRATEGY - Ramos Jiménez, Rosa Belén; Martínez Espinoza, Edison Fernando; García Llerena, Steven Bryan; Isín Vilema, David Manuel (mktDESCUBRE; Vol 1 No 3 (2020): Special Edition 1st International Marketing Congress, 2020)
SUMAK TARPUY, is an association of indigenous producers from Chimborazo, established whit the propose of production and market organic products, mainly quinoa. The company has the need to introduce and place a brand that identifies its product and allows it to take off in the market. This study is divided into three stages to acquire valuable information from the creation of the brand. For this, a documentary investigation was carried out about the product to know its strengths and weaknesses, and determine the concept. Subsequently, a field investigation was carried out, an interview to the director and the partners was applied, to obtain the client’s brief. Afterwards, a market study was carried out market in order to determinate the preferences of the consumer with respect to the product. A second field investigation was carried out, in which different supermarkets in the city of Riobamba were visited to observe and analyze the positive and negative characteristics of the brands competition. Finally, the brand design was guided in the verbal form represented by the name and the visual form represented by the logo, each element was determined based on the values achieved in the previous stages.